THE ANALYSIS OF CONSUMER PREFERENCES FOR SPORT NUTRITION PRODUCTS IN THE REPUBLIC OF NORTH OSSETIA – ALANIA - Z. V. Badalyan (Фармация и фармакология (Пятигорск))
Sport nutrition is a relatively new but rather prospective product group of pharmacy organizations range. The article presents the results of the study for consumers’ preferences for this group of products. We conducted the study using the methods of questionnaire and interview. The data obtained can be used by pharmacy organizations for the range formations and advertisement.